Emma on fire [large type] - Patterson, James, 1947-; Raymond, Emily, 1972- (Little, Brown and Company, 2025)
"Everyone at Ridgemont Academy knows what to expect from Emma Caroline Blake. Perfect grades. Perfect record. Perfect life. Then she stands up in class and commits an act so shocking her reputation will never recover. And that's exactly what Emma wants. In a world where the path forward is uncertain, expectation is the enemy. Emma on Fire is the ... story of one brave young woman--and her decision to live life as if everyone's future depends on it. Because it does"--